2007
DOI: 10.1007/s00374-007-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen conservation in soil and crop residues as affected by crop rotation and soil disturbance under Mediterranean conditions

Abstract: We investigated conservation and cycling of N under oat-oat and lupine-oat rotations in disturbed and undisturbed soil, when roots or roots plus aboveground residues were retained. Crop residues were labelled with 15 N in Year 1, and differential soil disturbance was imposed after harvest. In Year 2, plant growth, N transfer from residue into the various sinks of the second crop (plant, soil, and residual residues), and changes in microbial activity and numbers were determined. Oat biomass was greater after lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
15
1
Order By: Relevance
“…Amilcar) through their decomposition cycle (Ordóñez et al 2007). Similarly, Varennes et al (2007) found that oat biomass production was greater after lupine than after oat. They attributed this to a fact that lupine residues decomposed faster and sustained a great microbial activity, and in turn enhanced subsequent plant growth by providing more N than oat residues.…”
Section: Grain Yield and N Accumulationmentioning
confidence: 92%
See 1 more Smart Citation
“…Amilcar) through their decomposition cycle (Ordóñez et al 2007). Similarly, Varennes et al (2007) found that oat biomass production was greater after lupine than after oat. They attributed this to a fact that lupine residues decomposed faster and sustained a great microbial activity, and in turn enhanced subsequent plant growth by providing more N than oat residues.…”
Section: Grain Yield and N Accumulationmentioning
confidence: 92%
“…Studies have consistently revealed that legumes can increase the yields of subsequent crops, in particular when no fertilizer N was applied (Heenan 1995;Shah et al 2003;Mayer et al 2003;Varennes et al 2007). …”
Section: Grain Yield and N Accumulationmentioning
confidence: 98%
“…while treatment (sequence 3 + CR) resulted in significant increases in grain, straw and biological yields estimated by 69.1%, 49.7% and 56.2% respectively as compared with continues cereal crops sequence 1 (control). Wheat grain yield of treatment sequence 4 + CR was sig- Varennes et al, (2007). They investigated soil conservation under oat-oat and lupine-oat rotations when roots or roots plus aboveground residues were retained.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter case, a natural source of N must be sought. Legume species, for instance, are able to fix atmospheric N, meeting their own needs and transferring N to a non-legume crop after their N-rich tissues have been mineralized (De Varennes et al, 2007;Russelle, 2008). Legume species can be grown either as main crops in rotation and/or as cover crops or green manures in annual and perennial tree crops.…”
Section: Introductionmentioning
confidence: 99%